Ordinance No. 7, §§ 1, 6, 11, & 20, Selah Town Council (1919) (Selah, Washington). - (:unkn) unknown (General Publisher, 1919)
Any person in said Town except police officers and other persons authorized by law or have obtained proper authority so to do from the proper officer of said Town, who shall carry or wear in any manner concealed upon his or her person any dirk, dagger, stilletto, bowie-knife, sword, cane, gun, pistol, revolver, sling shot, metal knuckles or any other dangerous weapon or instrument which may be used to inflict injury upon the person of another.Any person in said Town except police officers and other persons whose duty it is to make arrests who shall draw, exhibit or attempt to use any deadly weapon with intent to do bodily injury to another, or with the intention of intimidating such other personAny person in said Town except mmmmmmmmpolice** officers engaged in the lawful discharge of their duty, and persons practicing at target shooting in a duly licensed shooting gallery, who shall fire off or discharge any gun, pistol or fire arm of any kind within the Town Limits
--
Keywords: CARRY - CONCEALED